TREMATODE INFECTION IN GASTROINTESTINAL TRACT OF DUCK FROM CHICKEN SLAUGHTERHOUSES IN BOGOR, WEST JAVA - Aviola, Lala; Tiuria, Risa; Nugraha, Budiman (Jurnal Kedokteran Hewan, 2025)
This study aims to identify and calculate the percentage of trematode infection in the gastrointestinal tract of ducks from chicken slaughterhouses in Bogor, West Java. This research used 10 ducks gastrointestinal tract, of which five came from chicken slaughterhouse in Bojong Gede and the rest came from a chicken slaughter house in Cibinong Market. The gastrointestinal tract was divided into four parts: the upper, middle and lower part of the intestine and cecum. Each feces sample was examined by making slides using native and floatation methods to identify the egg of endoparasite. Adult trematodes found in the sample were stained for genus identification. This study showed that 4 out of 10 ducks were positive for endoparasite infection. Trematodes found in this study were Echinostoma spp. (20%) along the small intestine, large intestine, and cecum. Echinostoma spp. egg was also found in this study another trematode genus found was Hypoderaeum spp. (10%) in the large intestine and cloaca.